2021
DOI: 10.3390/cancers13246228
|View full text |Cite
|
Sign up to set email alerts
|

Multicellular Effects of STAT3 in Non-small Cell Lung Cancer: Mechanistic Insights and Therapeutic Opportunities

Abstract: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer and accounts for 85% of lung cancer cases. Aberrant activation of the Signal Transducer and Activator of Transcription 3 (STAT3) is frequently observed in NSCLC and is associated with a poor prognosis. Pre-clinical studies have revealed an unequivocal role for tumor cell-intrinsic and extrinsic STAT3 signaling in NSCLC by promoting angiogenesis, cell survival, cancer cell stemness, drug resistance, and evasion of anti-tumor immunity. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 301 publications
(395 reference statements)
0
35
0
Order By: Relevance
“…STAT family members are both signal transducers and transcription factors [ 40 ]. Activation of STAT3 contributes to the development of many cancers [ 41 ], while the inhibition of STAT3 reportedly elicits apoptotic cell death and stimulates immune-related activities to eliminate cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT family members are both signal transducers and transcription factors [ 40 ]. Activation of STAT3 contributes to the development of many cancers [ 41 ], while the inhibition of STAT3 reportedly elicits apoptotic cell death and stimulates immune-related activities to eliminate cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of STAT3 contributes to the development of many cancers [ 41 ], while the inhibition of STAT3 reportedly elicits apoptotic cell death and stimulates immune-related activities to eliminate cancer cells [ 41 ]. Previous research has demonstrated the importance of tumor cell-intrinsic and extrinsic STAT3 signaling, as these activities encourage angiogenesis in non-small cell lung cancer by upregulating the expression of VEGF and other growth factors [ 40 ]. In this study, our results indicated the involvement of MEK, ERK, and STAT3 phosphorylation in CCL4-mediated promotion of Angpt2 expression and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the many negative effects of hyperactive STAT3 in the TME, a number of therapeutic interventions have been developed that target different stages of STAT3 signaling. Many of these drugs are already in or finishing clinical trials and have been extensively reviewed elsewhere [ 129 , 130 ]. However, we want to touch on a few of these which hold the most promise.…”
Section: Stat3 Inhibitionmentioning
confidence: 99%
“…Multiple small molecule STAT3 inhibitors have been tested in the last decade, and there are still many novel inhibitors which may one day reach clinical application [ 130 , 131 ]. One such STAT3 inhibitor, TTI-101, binds to the SH2 domain to prevent STAT3 homodimerization [ 132 ].…”
Section: Stat3 Inhibitionmentioning
confidence: 99%
“…As shown in Figure 6, CS3 and CS4 patients had lower IC 50 values, indicating that they may be more sensitive to these chemotherapy drugs. Previous studies have shown that inhibition of STAT3 expression may be the key to the combination of paclitaxel and cisplatin in NSCLC chemotherapy (49)(50)(51). miR-526b-3p promotes the response to cisplatin by inhibiting STAT3.…”
Section: Precision Treatment Recommendations For Luad Patientsmentioning
confidence: 99%